The effect of calcium hydroxide on the antibiotic component of Odontopaste® and Ledermix® paste. (27th November 2012) - Athanassiadis, M.; Jacobsen, N.; Nassery, K.; Parashos, P.
Abstract Aim To investigate the chemical interaction of calcium hydroxide with the antibiotics demeclocycline calcium in Ledermix® Paste and clindamycin hydrochloride in Odontopaste®. Methodology Validated methods were developed to analyse the interaction of calcium hydroxide in two forms, Pulpdent® and calcium hydroxide powder, with the two antibiotics. High‐performance liquid chromatography (HPLC) was used to analyse the mixed samples of the pastes and calcium hydroxide. The concentration of demeclocycline calcium over 0‐, 1‐, 18‐, 24‐, 72‐h and 7‐day time‐points was determined. The concentration of clindamycin hydrochloride over 1‐, 6‐, 24‐, 72‐h and 7‐day time‐points was determined. All tests with HPLC involved testing of the standard in duplicate alongside the samples. Linearity, precision and specificity of the testing procedures and apparatus were validated. Descriptive statistics are provided. Results The antibiotics in both Odontopaste® and Ledermix® Paste were affected by the addition of calcium hydroxide. When mixed with calcium hydroxide powder, Odontopaste® had a 2% loss of clindamycin hydrochloride over 7 days, but when mixed with Pulpdent®, there was a 36% loss over 7 days. Ledermix® Paste showed an 80% loss of demeclocycline calcium over 7 days when mixed with calcium hydroxide powder and a 19% loss when mixed with Pulpdent® over the 7‐day period. Conclusion The addition of calcium hydroxide to Odontopaste® or Ledermix® Paste results in reductions of the respective antibiotic over a 7‐day time period.